Constitutional and legal aspects of developing electoral system of the Republic of Kazakhstan - Ibrayeva, N.A. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
This work is one of the first scientific studies in Kazakhstan, built on the basis of empirical research methods – interviewing. The author of the article conducted a total of 25 interviews in the period from September 2021 to December 2022. Among the respondents surveyed, 10 persons were ordinary voters, 15 persons were experts in the field of electoral law (including scientists, teachers of higher educational institutions, members of election commissions, judges, public figures). The article contains the opinions of 5 respondents regarding the existing problems in the field of the electoral system and ways to solve them. The study was conducted with the aim to study the opinions of citizens directly involved in the electoral process, as well as the voters themselves. The scientific literature shows that research in the field of improving the electoral system has not yet been studied (especially empirically). Therefore, it will undoubtedly increase the contribution of research to science. In addition, during the research, the author of the article analyzed the legal acts of Kazakhstan in the field of elections, examined the experience of Poland, in order to adopt the positive aspects of practice in solving problems that hinder the development of the electoral system of the Republic of Kazakhstan and, if possible, apply it in the conditions of our state.